Peningkatan Kemampuan Analisis melalui Metode Outdoor Learning dan Keterampilan Sosial Mahasiswa pada Mata Kuliah Konsep Dasar IPS - Kiky Chandra Silvia Anggraini; Ana Fitri Agustin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The assumption of social studies as boring learning makes many students underestimate social studies learning which will have an impact on low analytical skills. The outdoor learning method was chosen because it encourages students to actively seek and build knowledge gained through learning outside the classroom. The application of Outdoor Learning method and social skills is expected to improve the ability to analyze. This study aims to examine the improvement of analytical skills through outdoor learning methods and social skills in basic social studies concepts. This study used a quantitative approach with a pre experimental design type one group pretest posttest. The subjects were 52 students. The data of this study were collected through social skills questionnaire and analysis ability test. Data analysis uses descriptive tests, prerequisite tests and hypothesis tests. Hypothesis testing using ANOVA test assisted by SPSS. Based on the tests carried out, there is a significant effect on the analysis ability of students, obtaining the results that there are differences in the analysis ability of students who have high social skills to obtain higher analysis skills through outdoor learning methods than students with low social skills. The results concluded that there was an increase in students' analytical skills after being given the outdoor learning method and there were differences in learning achievement abilities in students with high social skills and low social skills. This research is expected to help teachers, education managers, and policy makers in designing learning strategies that are more effective and relevant to the needs of students in the modern education era.